Why do banks target ROE? - George G. Pennacchi; Jo\~ao A. C. Santos (Federal Reserve Bank of New York, 2018)
Historically, nonfinancial corporations relied on performance targets linked to their EPS. Up until the 1970s, banks also appeared to follow a similar practice, but since then they have favored ROE. Equity investors seem to be aware of these differences because EPS growth is better at explaining nonfinancials' stock market value while ROE is better at explaining banks' market values. In this paper we present a model of a bank with fixed-rate deposit insurance that faces increasing competition that erodes its charter value. When under these conditions the bank chooses its capital to maximize shareholder value, its performance based on ROE is much better than its performance based on EPS. We argue that such a situation characterized the banking industry during the 1970s and explains why it adopted an ROE target.
Keywords: G21; G28; 330; banks; ROE; EPS